In the COVID-19 Era, Effects of Job Stress, Coping Strategies, Meaning in Life and Resilience on Psychological Well-Being of Women Workers in the Service Sector - Kim, Hee-Kyung (International journal of environmental research and public health, 2022)
The purpose of this study is to analyze the factors affecting the psychological well-being by using variables of job stress, coping strategies, meaning of life, and resilience to improve the quality of working life during COVID-19. The subjects were 135 adult women working for banks. Data were collected by having the subjects fill out a paper-and-pencil questionnaire, and analyzed through t-test, ANOVA, Pearson’s correlation coefficients, and multiple regression analysis. The subjects’ psychological well-being showed positive correlations with the social support-seeking coping mechanism (r = 0.33, p < 0.001), problem-solving-focused coping mechanism (r = 0.55, p < 0.001), meaning in life (r = 0.45, p < 0.001), and resilience (r = 0.37, p < 0.001). Psychological well-being showed negative correlations with job stress (r = −0.44, p < 0.001) and avoidance-focused coping mechanism (r = −0.28, p = 0.001). The factors affecting the psychological well-being were problem-solving-focused coping mechanism (β = 0.35, p < 0.001), job role stress (β = −0.24, p < 0.001), meaning inlife (β = 0.29, p < 0.001), avoidance-focused coping mechanism (β = −0.23, p < 0.001), and resilience (β = 0.15, p = 0.023). It is necessary to formalize psychological intervention to induce the improvement of the quality of work life by increasing the psychological well-being of working women during the COVID-19 pandemic. It is suggested that intervention is made in consideration of variables identified as influencing factors to increase the psychological well-being of women workers.